SUPERVISION AND CONTROL OF BUSINESS SUBJECTS IN THE CONTEXT OF THE SYSTEM CONSTRUCTION OF ANTI-CORRUPTION MECHANISM - Юлдашев, Сергій Олексійович; Сєров, Сергій Леонідович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Goal: to identify, in the context of creating a theoretical and methodological framework for improving the legal control of economic activity, its problems, and formulation of corresponding specific constructive proposals. Methods: when writing the article, general scientific methods of research were used. Results: supervision and control are more effective in reaching their goals, are better, more transparent and more understandable to all, if they act in isolation, personally, autonomously and in a coherent, systematic way with other control and management bodies when this interaction is regulated, regulated. There should be systematically regulated and regulated procedures for the implementation of each of the above-mentioned functions with an attachment to the performers of each stage of supervision and control. It is advisable to create a state anti-corruption mechanism in the legislative framework, in the center of which would be such functions as supervision and control. Under the anticorruption mechanism we will understand the totality of supervisory and control bodies, as well as technologies for the implementation of these functions. Discussion: systemic linking (at the level of linking «inputs» and «outputs») of the activities of organs, organizations, private individuals, who are now acting personally, autonomously, is one unit that aims to neutralize corruption. To resolve the issues, the concept of the creation and maintenance of the state anti-corruption mechanism was proposed.